2008
DOI: 10.1111/j.1600-0897.2008.00652.x
|View full text |Cite
|
Sign up to set email alerts
|

ORIGINAL ARTICLE: Ecology of Danger‐Dependent Cytokine‐Boosted Spontaneous Abortion in the CBA × DBA/2 Mouse Model: II Fecal LPS Levels in Colonies with Different Basal Abortion Rates

Abstract: A high endogenous rate of abortion and cytokine (or stress) boosted abortion in the CBA x DBA/2 model is not explained by the LPS content of feces. Possible explanations include: fecal LPS does not reflect small intestinal LPS, there are additional TLR signals besides LPS that are important and endogenous stress levels may be higher in high-abortion-rate colonies, so permeability of the intestine (and Th1 cytokine levels) may be already higher. These data have implications for studies on the role of flora in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…Addition of reagents led to formation of a magenta derivative that absorbs light at 545 nm. For fecal endotoxin concentration, 20 µg of feces from cecum was placed in 50 ml of PBS in a pyrogen-free tube and sonicated for 1 hr on ice [22]. After centrifugation at 400 g for 15 min, the upper 30 ml was collected, sterilized by filtration through a 0.45 µm filter followed by re-filtration through a 0.22 µm filter, and inactivated for 10 min at 70°C.…”
Section: Methodsmentioning
confidence: 99%
“…Addition of reagents led to formation of a magenta derivative that absorbs light at 545 nm. For fecal endotoxin concentration, 20 µg of feces from cecum was placed in 50 ml of PBS in a pyrogen-free tube and sonicated for 1 hr on ice [22]. After centrifugation at 400 g for 15 min, the upper 30 ml was collected, sterilized by filtration through a 0.45 µm filter followed by re-filtration through a 0.22 µm filter, and inactivated for 10 min at 70°C.…”
Section: Methodsmentioning
confidence: 99%
“…9,10 Other authors showed that high frequency of abortion in the CBA/J ϫ DBA/2 model may be explained by exposure to bacterial lipopolysaccharides (LPSs) at the time of mating 8,11,12 or increased absorption of LPS from intestinal flora. 7,[11][12][13] A variety of inflammatory stimuli, including bacterial cell products and components of the complement system, are known to promote the expression of tissue factor (TF) on the surface of endothelial cells, monocytes, and neutrophils.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Other authors showed that high frequency of abortion in the CBA/J ϫ DBA/2 model may be explained by exposure to bacterial lipopolysaccharides (LPSs) at the time of mating 8,11,12 or increased absorption of LPS from intestinal flora. 7,[11][12][13] A variety of inflammatory stimuli, including bacterial cell products and components of the complement system, are known to promote the expression of tissue factor (TF) on the surface of endothelial cells, monocytes, and neutrophils. [14][15][16] In view of previous studies showing that aberrant TF expression may be responsible for thrombosis, we considered the possibility that increased TF expression induces pathological activation of the coagulation pathway, placental failure, fetal death, and growth restriction in this model of spontaneous abortion.…”
Section: Introductionmentioning
confidence: 99%
“…We suggest that TLRs are excessively activated to some extent in functional protein expression but not gene expression at the maternal-fetal interface of mice undergoing spontaneous abortions. Researchers showed that high frequency of abortion in the CBA/J × DBA/2 model may be explained by exposure to bacterial LPSs at the time of mating [35] or increased absorption of LPS from intestinal flora [23,24]. Thus, the activation of TLRs in abortion groups might induce by the accumulation of LPS.…”
Section: Discussionmentioning
confidence: 99%